2009
DOI: 10.1287/mnsc.1080.0942
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Time Inconsistency

Abstract: Preference between two future outcomes may change over time--a phenomenon labeled as time inconsistency. The term "time inconsistency" is usually used to refer to cases in which a larger-later outcome is preferred over a smaller-sooner one when both are delayed by some time, but then with the passage of time a preference switches to the smaller-sooner outcome. The current paper presents four empirical studies showing that time inconsistency in the other direction is also possible: A person may prefer the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…For money, our findings on increasing impatience confirm previous evidence (e.g. Attema et al 2010;Sayman and Öncüler 2009;Loewenstein 1987;Takeuchi 2011;Chesson and Viscusi 2003;Rubinstein 2003). For health, only indirect evidence of increasing impatience existed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For money, our findings on increasing impatience confirm previous evidence (e.g. Attema et al 2010;Sayman and Öncüler 2009;Loewenstein 1987;Takeuchi 2011;Chesson and Viscusi 2003;Rubinstein 2003). For health, only indirect evidence of increasing impatience existed.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have found increasing impatience for money (e.g. Attema et al 2010;Sayman and Öncüler 2009;Scholten and Read 2006;Loewenstein 1987;Takeuchi 2011). For health, only indirect evidence of increasing impatience exists .…”
Section: Introductionmentioning
confidence: 99%
“…And, third, there is a common difference effect (Loewenstein & Prelec, 1992), with the rate of discounting over a given interval being lower the later the interval begins (e.g., McAlvanah, 2010;Scholten & Read, 2006; but see Sayman & € Onc€ uler, 2009;Read, Frederick, & Airoldi, 2012): The representative agent will prefer $200 in 2 years to $100 in 1 year. These preference patterns are all accommodated by the hyperbolic discounting model, as summarized in Table 1. There are, however, anomalies that the hyperbolic discounting model, and indeed all delay discounting models, cannot accommodate.…”
Section: Introductionmentioning
confidence: 99%
“…For intertemporal choices, the tradeoffs involve time and amount-smaller sooner rewards compared with against larger later rewards. For some, the perfect real world example may be the decision of whether to endure lower (or no) wages during college so as to permit greater earnings later.The dominant method for investigating intertemporal choices in the lab has been to elicit choices between smaller-sooner and larger-later amounts of money (see, e.g., Ainslie & Haendel, 1983;Hardisty & Weber, 2009;Kirby, 1997;Read, 2001;Sayman & Öncüler, 2009;Weber et al, 2007;Zauberman, Kim, Malkoc, & Bettmann, 2009). Most of this research has focused on how discount rates are influenced by differences in the magnitude or timing of those outcomes (e.g., Benzion, Rapoport, & Yagil, 1989;Keren & Roelofsma, 1995;Kirby & Herrnstein, 1995;Scholten & Read, 2006;Thaler, 1981).…”
mentioning
confidence: 99%